Forest and Land Fire Disaster Risk Assessment Using Geographic Information Systems in Arut Selatan District, West Kotawaringin Regency, Central Kalimantan Province - Tara Adi Prakoso; Retno Utami Agung Wiyono; Gusfan Halik (Journal of Applied Geospatial Information, 2025)
Kotawaringin Barat Regency, Central Kalimantan Province, has six sub-districts, namely Kumai District, Arut Selatan District, Arut Utara District, Pangkalan Lada District, Pangkalan Banteng District, and Kotawaringin Lama District, all of which are areas prone to natural disasters. One of them is forest and land fires. In recent years, there have been many forest and land fires in the Kotawaringin Barat Regency area. Starting in 2022, there were around 75 forest and land fires; in 2023, there were around 201 incidents; and in 2024, there were around 36 incidents, all of which were in the Arut Selatan District and Kumai District. With the occurrence of forest and land fires, most of them in the two sub-districts, namely Kumai and Arut Selatan Districts, this study took the location of Arut Selatan District. The assessment of forest and land fire disaster risks uses spatial analysis methods. To find the weight of hazard, vulnerability, and capacity using secondary data processed with the formula according to the Regulation of the Head of BNPB Number 2 of 2012 concerning disaster risk assessment using the Excel application. The results of the assessment of the risk of forest and land fires in the South are dominated by high classifications of 9 villages/sub-districts with a percentage of 83.8% of the total area. While for the moderate classification of 5 villages/sub-districts with a percentage of 2.7% of the total area and moderate classification of 6 villages/sub-districts with a percentage of 13.5% of the total area. With the high risk of forest and land fires because the percentage of hazards and vulnerabilities is still high and the percentage of capacity is still classified as moderate. For this reason, it is necessary to increase capacity in dealing with forest and land fires to reduce the risk of forest and land fires that occur.